Suelos Y Karst, Origen De Inundaciones Y Hundimientos En Chetumal, Quintana Roo, México - Fragoso-Servón, Patricia; Pereira-Corona, Alberto (European Scientific Journal, ESJ, 2018)
The Mexican Caribbean and its main cities have the highest population growth rate in Mexico. This work goal was to analyze the growth of the city of Chetumal and the geopedological characteristics in which it has been developed, to identify potential hazards and thereby improve development programs. The methodology consisted in the study of geopedological characteristics and the analysis of land use changes in the city over time. The main problems of Chetumal are floods and subsidence. Floods are more common in areas where Gleysols soils are found in low-lying areas. The subsidence is associated to Leptosols with a phreatic mantle at a shallow depth where the precipitations favors dissolution of rock. The extrapolation of the relationships between geopedological conditions and the area occupied by the city, allows us to suppose that areas which the current Urban Development Program proposes for future city expansion will develop the same problems of subsidence and flooding as the areas already built in sites with similar conditions.